Implementation of a centralized HPV-based cervical cancer screening programme in Tuscany: First round results and comparison with the foregoing Pap-based screening programme. (June 2022) - Carozzi, Francesca; Burroni, Elena; Confortini, Massimo; Pompeo, Giampaolo; Bisanzi, Simonetta; Cellai, Filippo; Paganini, Irene; Mantellini, Paola; Iossa, Anna; Lelli, Lisa; Di Pierro, Carmelina; Matucci, Marzia; et al.
Objective: To evaluate performance of the first round of HPV-based screening in Tuscany region and compare it with the prior round of Pap-based screening Setting: Tuscany region of Italy, where HPV-based cervical cancer screening started in 2013, with a strong level of centralization screening tests at the Regional Laboratory for Cancer Prevention (ISPRO). Methods: The transition from Pap- to HPV-based screening was initiated for older women and at 3 out of 12 Tuscany Local Health Units (LHUs). Data from the Florence and Grosseto LHUs (about 300, 000 women) were analysed and performance screening indicators estimated. Results: HPV-based indicators recorded good performance, with increased compliance vs. the Pap-based programme. We registered a substantial decrease in waiting times from sampling to test reporting, probably related to the centralization strategy. Since the screening protocol was the same and conducted at a single laboratory, we could hypothesize that the difference in HPV positivity (6.8% in Florence vs. 8.4% in Grosseto) was due to a real difference in HPV prevalence among women of the two LHUs. The transition to HPV-based screening led to a significant increase both in colposcopy referral rate (4.3% vs. 1.2%) and CIN2+ detection rate (8.3‰ vs. 3.4‰). Conclusions: HPV-based is more effective in detecting high-grade precancerous and cancerous lesions than Pap-based screening and is characterized by an "anticipatory effect" in the detection of CIN2+ lesions. The transition from Pap-based to HPV-based screening programme should include increased resources dedicated to colposcopy services. Centralization in a laboratory with long experience in this field promotes efficiency of the screening process.